Молекулярні маркери в прогнозуванні гетерозису у кукурудзи - Букрєєва, Н.І.; Доменюк, В.П.; Бєлоусова, А.О.; Соколов, В.М.; Сиволап, Ю.М. (Фактори експериментальної еволюції організмів, 2014)
Aims. Selection procedure based on the use of molecular markers, the so-called marker-assisted selection (MAS), has advantages over conventional selection methods, since MAS uses close associations between genetic markers and loci of important agronomic traits. Methods. The parental material, that is, the maize lines GK26 and Mo17, the segregating population (GK26 x Mo17) F₂ – F₆ and testers (used as pollinators on hybridization plots with parental recombinant inbred lines (RILs)) Od308MV, Od221MV and Od329, were combined with ISSR-, RAPD-,SSR-analysis of genetic diversity to characterize the populations. Results. Parental lines GК 26 and Мо 17 and lines-testers of Od 221 MB, Od 308 MB, Od 329 polymorphism was analyzed by SSR-PCR and genotyping RILs populations F₄, F₆ was conducted. The cluster and correlation analyses of RIL populations and dependence between the genetic distance and hybrid performance levels were determinated. DNA-based prediction breeding of parental genotypes for creating of testcross with high performance using microsatellite marker information was simulated. The results allowed to predict high performance hybrids group and reduce analyzed samples on 70–80 %. Conclusions. The technology of prediction based on association with DNA markers and quantitative traits in maize populations was created. It was allowed to improve the genetic base of maize populations and their use for source material for heterosis breeding. Molecular markers are an effective tool for solving problems of breeding, including the use of heterosis problems and improve the quality of the crop.